Spectral proper transformation and application to gust response prediction of structures - Hoa, Le Thai; Anh, Nguyen Dong (Vietnam Journal of Mechanics, 2007)
Random turbulent loading on engineering structures which immersed in the atmospheric turbulent flow is often represented as the multi-dimensional and/ or multivariate Gaussian random loading processes. Gust response prediction, however, usually burdens a lot of computational difficulties due to turbulent loading projection on the generalized structural coordinates. In these cases, the decomposition techniques must be required to decouple the multi-variate turbulent loading into the independently generalized turbulent forces, then is associated with the generalized structural modes. This paper will present the proper orthogonal decomposition using the spectral proper transformation in the frequency domain to decouple the multi-variate turbulent loading processes. New approach in the gust response prediction of structures will be formulated with numerical example of cable-stayed bridge.